Functional traits for salinity tolerance in differently adapted populations of Fimbristylis complanata (Retz.). Issue 12 (15th October 2021) - Kaleem, Muhammad; Hameed, Mansoor
Abstract: Functional modifications in three populations of Fimbristylis complanata collected from differently salt effected habitats were evaluated. The populations were established in pots and treated with five NaCl levels (0, 100, 200, 300, and 400 mM). Population SH (collected from the highest salinities, ECe 37.94 dS m −1 ) exhibited better osmotic adjustment because of the higher accumulation of organic osmolytes under high salinities and was ranked as highly tolerant. Other features like an increased concentration of chlorophyll pigments ensured maintenance of photosynthetic capability, and accumulated higher K + and Ca 2+ contents that minimized the toxic effect of Na + and maintained ion homeostasis. Salinity tolerance in the Lillah–Khewra foothills (LR) population (collected from moderately saline site, ECe 31.36 dS m −1 ) relied on the maintenance of shoot dry weight (SDW) and shoot and root length (RL) with a parallel accumulation of organic osmolytes and shoot Ca 2+ . This species is a stem succulent and can store excessive amount of salt in storage parenchyma, as indicated by the accumulation of high concentration of Na + in shoot. The SH population, in particular, can be rated as the best for phytoremediation of salt-affected soils that accumulated more Na + than other populations and concentration of osmolytes for turgor maintenance under high salinities. Novelty statement Fimbristylis is less explored, particularly no information available on salt tolerance of F. complanata exists in the literature.